Pendampingan Kelompok Pengrajin Atap “Katu” untuk Meningkatkan Kualitas Produksi sebagai Material Penunjang Pariwisata Berkelanjutan: Assisting “Katu” Roof Craftsman Groups to Improve Production Quality for Sustainable Tourism Materials - Kindangen, Jefrey I.; Mandey, Johansen; Kalalo, Loudy (Sam Ratulangi University, 2025)
The continued growth of the tourism sector has increased the demand for natural and environmentally friendly building materials. Katu roofing, made from sugar palm leaves, holds strong potential as a supporting material for tourism facilities due to its aesthetic value, thermal performance, and use of local sustainable resources. However, artisans face challenges such as inconsistent production quality, limited market reach, and the absence of formal organizational structures. This Community Partnership Program (PKM) aims to improve production quality, strengthen marketing capacity, and promote the formation of artisan groups in North Minahasa Regency through outreach activities, production training, and marketing assistance. The program results indicate improved understanding of raw material processing, more aesthetically refined product designs, and increased awareness of the importance of collective organization to enhance market competitiveness. The program recommends stronger local government support, particularly in developing production centers and providing exhibition spaces to facilitate more effective product marketing. ABSTRAK Pembangunan sektor pariwisata yang terus berkembang meningkatkan kebutuhan akan bahan bangunan yang alami dan ramah lingkungan. Atap katu, berbahan daun pohon aren, memiliki potensi besar sebagai material penunjang pariwisata karena nilai estetika, kinerja termal, dan pemanfaatan sumber daya lokal. Namun, pengrajin menghadapi kendala berupa kualitas produksi yang belum konsisten, pemasaran terbatas, dan belum adanya kelembagaan usaha. Program Kemitraan Masyarakat (PKM) ini bertujuan memperbaiki kualitas produksi, memperkuat kapasitas pemasaran, dan mendorong pembentukan kelembagaan pengrajin atap katu di Kabupaten Minahasa Utara melalui penyuluhan, pelatihan produksi, dan pendampingan pemasaran. Hasil kegiatan menunjukkan peningkatan pemahaman pengrajin terhadap pengolahan bahan baku, desain produk yang lebih estetis, serta pentingnya organisasi kelompok untuk meningkatkan daya tawar. Program ini merekomendasikan dukungan pemerintah daerah dalam pembentukan sentra produksi dan penyediaan ruang pamer untuk memfasilitasi pemasaran yang lebih efektif.